A new bee fly species of the genus Phthiria (Diptera, Bombyliidae, Phthiriinae, Phthiriini) from the west of Iran - Farhangi, Seyed Vahid; Nozari, Jamasb; Gharali, Babak (Zootaxa, 2023)
Phthiria portokali sp. nov. is described and illustrated from the west of Iran based on specimens collected by white pan traps. The new species is unique in having a large tortoise-shell-shaped orange pattern on the dorsum of the mesonotum of the female specimens. This character has not been seen among the other species described from the Palaearctic Region.